The representative scientific results of the China Seismo-Electromagnetic Satellite - Zhima Zeren; Yanyan Yang; Rui Yan; Zhenxia Zhang; Jie Wang; He Huang; Song Xu; Hengxin Lu; Na Zhou; Jianping Huang (Earthquake Research Advances)
The China Seismo-Electromagnetic Satellite (CSES-01) launched on February 2, 2018, has been steadily operating in orbit for more than six years, exceeding its designed five-year lifespan expectation. The evaluation results suggest that the satellite platform and the majority of payloads are performing well, and still providing reliable measurements. This report briefly introduces the representative scientific results obtained from CSES-01's five-year observations. The first result is the long-term global geophysical field data accumulated for the first time, including the global geomagnetic field, the electromagnetic field and waves in a broad frequency band, the in-situ and profile ionospheric plasma parameters, and the energetic particles. The second result is that a series of data processing and validation methods were obtained, and some of the methods are unique worldwide. The third result is that the geomagnetic field, lithospheric magnetic field, and ionospheric electron density 3D models were built based on CSES-01’ s data. The fourth result is that statistical features of seismic-ionospheric disturbances were revealed and the direct observational evidence for the electromagnetic wave propagation models in the lithosphere-atmosphere-ionosphere was also confirmed. The fifth result is the physical processing of the space weather events was clearly described, showing CSES-01's good capability of monitoring space weather conditions.